2018
DOI: 10.1038/s41598-018-26413-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associations of Illicit Drug and Polydrug Use in People Living with HIV in Vienna

Abstract: We aimed to determine the prevalence of drug and polydrug use in people living with HIV in Austria for the first time for which a two center cross-sectional study was performed. Participants were recruited from consecutive patients during their regularly scheduled visits. In total 438 participants were included in the analysis. For this study we used paper-pencil and online-based questionnaires. The prevalence of illicit drug use was 60.5%; with cannabis use at 31.5%, nitrates at 31.5%, sildenafil/tadalafil at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The frequency of consumption of alcoholic beverages and being younger were also associated with RDU, albeit at a lower intensity. These results confirm the findings of other studies, where a higher prevalence of RDU amongst those of a younger age [3,59,60] and a higher incidence of STIs in the HIV population [3,[61][62][63] were found. Legal drugs such as Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of consumption of alcoholic beverages and being younger were also associated with RDU, albeit at a lower intensity. These results confirm the findings of other studies, where a higher prevalence of RDU amongst those of a younger age [3,59,60] and a higher incidence of STIs in the HIV population [3,[61][62][63] were found. Legal drugs such as Fig.…”
Section: Discussionsupporting
confidence: 91%
“…For example, our results were similar to those found by Daskalopoulou et al [5] in the United Kingdom, although direct comparison is not possible since that study evaluated last-three-months consumption. Grabovak et al [39] found a moderately higher prevalence of drug use in PLHIV in Austria but their analysis included sildenafil/tadalafil, categorized as ‘other substances’ in our study. In contrast, our prevalence results were higher compared with other studies in France [40] or Scotland [37] although, again, differences in time frame make comparisons.…”
Section: Discussionmentioning
confidence: 88%
“…Cocaine use is common among persons with chronic human immunodeficiency virus (HIV) infection, with prevalence estimates for current or recent use ranging from 5 to 30% [1][2][3][4][5][6], compared with 2% in the US general population [7]. Previous studies have shown that cocaine use accelerated HIV progression [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%